Protein and Cholesterol Levels of Duck Eggs after the Addition of Nanochitosan as a Feed Additive - Sunarno Sunarno; Elsa Ayu Kusuma; Agung Janika Sitasiwi (Biosaintifika: Journal of Biology & Biology Education, 2023)
Nanochitosan is a polysaccharide that can be used as a feed additive to improve the chemical quality of eggs. Protein and cholesterol levels are indicators of the chemical quality of eggs that affect egg weight. This study aims to analyze the effect of nanochitosan as a feed additive on improving the chemical quality of eggs in terms of protein content, cholesterol content, egg white weight, egg yolk weight, and duck egg weight. This study was designed in a completely randomized design (CRD) consisting of 5 treatments (0; 2.5; 5; 7.5; 10 g nanochitosan/kg feed) with 5 replications. Treatment of feed was given for 8 weeks. Variables measured included protein content, cholesterol level, egg white weight, egg yolk weight, and duck egg weight. Data was analyzed using ANOVA at 5% significance. The results showed that nanochitosan as a feed additive had a significant effect on increasing protein content, egg white weight, egg yolk weight, egg weight and cholesterol reduction. The conclusion of this study is that nanochitosan can be used as a feed additive that has potential to improve the chemical quality of duck eggs. The novelty of this research is the use of nanochitosan as a feed additive to improve the performance of livestock in increasing protein levels and reducing cholesterol levels in pengging duck eggs. The results of this study are expected to open up opportunities regarding the use of nanochitosan as a feed additive in various other local ducks in Indonesia.